Higher Education Reform: Signs from the End of the Century International Debate - Roberto Rodríguez Gómez (Universidad Autónoma de Baja California, 2000)
During the last ten years of the 20th century, there has been an extensive debate on the worldwide problem of higher education. This article aims at identifying some of the outstanding speakers who have greater impact; as well as briefly summarizing the lines of discussion present in the debate. The text is divided into two sections. The first one deals with the role of different international organizations in defining the public policies on higher education, particularly in Mexico and the Latin American region. The second one includes a commented description of three national cases, where some pronouncements emerged after the constitution of special commissions for the study of higher education: The French case, the United Kingdom's and the United States' case.